Analisis Mutu Sumber Daya Manusia Terhadap Pelayanan Pelanggan Pada PT. Katingan Timber Celebes Di Makassar - Roswiyanti Roswiyanti; Muhtazib Muhtazib (Universitas 17 Agustus 1945 Semarang, 2022)
The research objective is to determine the significance of the influence of human resource quality on customer service at PT. Katingan Timber Celebes (KTC) in Makassar, South Sulawesi Province. And to find out the variables that most influence customer service at PT. Katingan Timber Celebes (KTC) in Makassar, South Sulawesi Province. This research uses quantitative research methods. The independent variables are the variables of expertise, skills, experience and discipline which together have a significant influence on the company's customer service at PT. Katingan Timber Celebes (KTC) in Makassar, South Sulawesi Province. Of all the influencing factors (variables), it turns out that the skill variable is the most influential on the company's customer service at PT. Katingan Timber Celebes (KTC) in Makassar, South Sulawesi Province. This can be seen where the regression coefficient value is 0.375 which is greater than the regression coefficient value of the other independent variables.